2020
DOI: 10.1177/0733464820910028
|View full text |Cite
|
Sign up to set email alerts
|

In-Home Technology Training Among Socially Isolated Older Adults: Findings From the Tech Allies Program

Abstract: Technology has the potential to increase social connectedness among older adults, but one-third do not use the internet. We formed a community partnership, Tech Allies, providing tablets, broadband, and 1:1 training to isolated older adults. In a pragmatic pilot trial, participants were randomized into intervention ( n = 44) and waitlist ( n = 39) groups. Volunteers provided eight weekly, in-home iPad lessons. Surveys assessed self-reported loneliness, social support, technology use, and confidence at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…The frequency of internet use significantly increased. These findings are consistent with past studies that demonstrated increased internet use for communication among older adults after training participation (Bertera et al, 2007;Damnee et al, 2019;Fields et al, 2020;Ibarra et al, 2020;Woodward et al, 2011). Hypotheses 1 and 3 were supported, and Hypothesis 2 was partially supported.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The frequency of internet use significantly increased. These findings are consistent with past studies that demonstrated increased internet use for communication among older adults after training participation (Bertera et al, 2007;Damnee et al, 2019;Fields et al, 2020;Ibarra et al, 2020;Woodward et al, 2011). Hypotheses 1 and 3 were supported, and Hypothesis 2 was partially supported.…”
Section: Discussionsupporting
confidence: 91%
“…Computer and internet training for older adults has shown that it can assist them in using the computer and internet more regularly for communication purposes, which can serve to decrease the digital divide (Bertera et al, 2007;Damnee et al, 2019;Fields et al, 2020;Ma et al, 2020;Woodward et al, 2011;Xie & Bugg, 2009). In a randomized field trial for older adults (60 years and older) of a 6-month computer and internet training programme (Woodward et al, 2011), participants in the experimental group demonstrated improvements in computer usage self-efficacy.…”
Section: Impacts Of Intervention Programmes On Computer and Internet Usagementioning
confidence: 99%
See 3 more Smart Citations